Situation Analysis of Child Health and its Related Policy in Nepal (Patan Pragya, 2019)
The main aim of this paper is to assess the current situation of child health based on childhood mortality, nutritional status, and vaccination coverage and also reviews the existing government policies in relation to improve the child health. The study shows Nepal has achieved significant improvement in the child health situation as measured by the impressive progression of childhood mortality level, improved nutritional status and vaccine coverage and micronutrient intake. For this achievement Government of Nepal, has progressively introduced policies programme and strategies to make improvement in the health status of women and children and all Nepali Citizens.